Political Internet Memes In Indonesia: A Case Study Of The 2019 Indonesian Presidential Election - Mahadian, Adi Bayu (2022)
Internet meme has become a relatively new language of political expression in Indonesia. However, the Indonesian government considers internet memes a threat, and some citizen has been arrested for an accusation of insulting the president with the internet memes and escalating polarization in the society. The polarization made the 2019 Indonesian presidential election the most intense in the Reformation era. Using the political internet meme in the political discourse toward the Presidential Election becomes rough and harsh. This research examined how Indonesian society used internet memes to discuss political issues toward the 2019 Presidential Election. This study investigated the discourse and how it is discussed in the political discourse in the context of contemporary political humour toward the 2019 Presidential Election. Using the 'Meme Pilpres 2019' keywords on Google's search engine, the research collected 583 internet memes. Then, the researcher selected the internet meme based on specific criteria: it contains images, text, or any other element representing both presidential candidates, and it contains humour with more than a single associative context. The data resulted in 126 internet memes being categorized into themes. Three main themes of discourses were obtained: religion, political ideology, and national leader's characteristics. The research discovered three findings according to the depth analysis of the internet memes on each theme. First, taboo and the prohibited issue (such as an Islamic discourse) were articulated as the story background of the humourous internet memes. Then, the story background could be articulated with another associative context to build a humourous internet meme.